ИЛИМИЙ - ПЕДАГОГИКАЛЫҚ ИЗЕРТЛЕЎ МЕТОДЛАРЫ - Ешмуратов, Х. (FAN va JAMIYAT, 2016)
The article deals with the essence and content of the main methods of scientific- pedagogical investigations and their significance in ensuring the effectiveness of the research. The author of the article distinguishes spiritual and intellectual qualities necessary for a person who deals with the scientific research work.